2014
DOI: 10.1530/eje-13-0651
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE: Impact of iodine supplementation in mild-to-moderate iodine deficiency: systematic review and meta-analysis

Abstract: Background: Although the detrimental effects of severe iodine deficiency are well recognised, the benefits of correcting mild-to-moderate iodine deficiency are uncertain. Objectives: We undertook a systematic review of the impact of iodine supplementation in populations with mildto-moderate iodine deficiency. Methods: We searched Medline and the Cochrane library for relevant articles published between January 1966 and April 2013, which investigated the effect of iodine supplementation on maternal and newborn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 76 publications
9
87
1
20
Order By: Relevance
“…To isolate the effect of long-term iodine intake, we restricted these analyses to participants who did not report the use of supplements containing iodine in the FFQ. Previous studies have indicated that long-term iodine intake might be more important for thyroid function during pregnancy than recent supplement use (39). Indeed, we also found that the associations between iodine FIGURE 3 Associations between maternal iodine intake from food in pregnancy and internalizing (A, B) and externalizing (C, D) child behavior problems at the age of 3 y in the Norwegian Mother and Child Cohort Study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…To isolate the effect of long-term iodine intake, we restricted these analyses to participants who did not report the use of supplements containing iodine in the FFQ. Previous studies have indicated that long-term iodine intake might be more important for thyroid function during pregnancy than recent supplement use (39). Indeed, we also found that the associations between iodine FIGURE 3 Associations between maternal iodine intake from food in pregnancy and internalizing (A, B) and externalizing (C, D) child behavior problems at the age of 3 y in the Norwegian Mother and Child Cohort Study.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies on iodine supplement use in pregnancy and child neurodevelopmental outcomes in areas with mild-to-moderate ID have shown inconsistent results (3,39,48), and to our knowledge there are no randomized controlled trials published to date. In this study we examined the associations in women with iodine intake from food below and above the EAR (160 mg/d) separately because the effect of supplemental iodine might depend on previous iodine status.…”
Section: Figurementioning
confidence: 88%
“…While many countries have mandatory iodizes salt programmes in Portugal only two recommendations are ongoing; DGS suggests supplementation for pregnant women [32] and Directorate-General for Education (DGE) the iodized salt use for school canteens [44]. However, although Universal salt iodine can eliminate specific supplementation [45], such as pregnancy and lactation periods [32,35], our results showed that iodine supplementation is not a current practice. Obstetricians and pediatrics medical practice and mothers did not present consistent information regarding this subject.…”
Section: Discussionmentioning
confidence: 82%
“…В метаанализ были включены 9 рандомизи-рованных контролируемых исследований и 8 описа-тельных исследований. Было выявлено, что у детей школьного возраста на фоне йодопрофилактики было отмечено умеренное улучшение способности рассуждать и повышение общего когнитивного ин-декса [44].…”
Section: дефицит йода и когнитивное развитие детейunclassified